The letters of Samuel Wesley: social and professional correspondence, 1797-1837 - Olleson, Philip (2000)
The life of the composer and organist Samuel Wesley (1766-1837) encompassed momentous changes in British society. Born in the early years of the reign of George III, Wesley died in the first months of the reign of Victoria. He saw equally momentous changes in music. As a child he was taught by musicians who remembered and in some cases had played for Handel; in adult life, he witnessed the introduction of the music of Haydn, Mozart, and Beethoven into England, and late in his career saw the visits to London of Liszt, Weber, and Mendelssohn. Wesley's life on both a personal and professional level was highly unconventional. Born into the first family of Methodism - his father was the hymn-writer Charles Wesley (1708-88), his uncle was John Wesley (1703-91) - he converted in his teens to Roman Catholicism and spent most of his life alienated from his family and from his Methodist upbringing. His marriage to Charlotte Louisa Martin in 1793 followed years of family opposition and a period when the couple lived together unmarried. In 1810 he left her for his teenage housekeeper, with whom he lived until his death. His professional career was brilliant but uneven, bedevilled by periods of mental illness which left him incapacitated for long periods. Wesley was a prolific correspondent: over 600 letters out of a far larger number of letters that he is known to have written are extant. The letters fall into two fairly distinct categories: those to members of his family, and those to correspondents outside the family. This division is paralleled to a large degree in the subject matter of the letters. In general, Wesley kept his family and his professional and social life well apart. He only rarely discusses family matters rarely in his social and professional letters; conversely, although there are many mentions of his social and professional life in the family correspondence, they do not form a very large proportion of it as a whole. The two sequences of letters are thus largely self-contained. The bulk of Wesley's discussions of music are contained in the social and professional letters, and these form the largest and most important collection of letters by an English musician of the late eighteenth and early nineteenth centuries. This edition brings together all such letters from 1797 until Wesley's death in 1837. It also includes a few family letters where the subject matter is wholly or largely music: further details are given in the Textual Introduction. It can therefore be seen as the first part of a complete edition of Wesley's letters. The second part, containing the family letters, will, I hope, follow in due course.